Democratizing Rule Development - Michael Sant'Ambrogio; Glen Staszewski (Washington University Law Review, 2021)
Agencies make many of their most important decisions in rulemaking well before the publication of a Notice of Proposed Rulemaking (NPRM), when they set their regulatory agendas and develop proposals for public comment. Agencies’ need for information from outside parties and openness to alternative courses of action are also generally at their greatest during these earlier stages of the rulemaking process. Yet regulatory agenda setting and rule development have received virtually no scholarly attention. The literature generally treats what happens before publication of the NPRM as a “black box” and suggests that agenda setting and rule development are primarily influenced by political considerations and pressure from well-organized groups. Other interested stakeholders, including regulatory beneficiaries, smaller regulated entities, state, local, and tribal governments, unaffiliated experts, individuals with situated knowledge of the regulatory issues, and members of the general public, are routinely absent. While there is undoubtedly much truth to this understanding, a recent study we conducted for the Administrative Conference of the United States unearthed significant efforts by numerous federal agencies to engage the public long before the publication of an NPRM. The existing efforts, however, tend to be relatively unstructured, unsystematic, and ad hoc. Moreover, many opportunities for public engagement are voluntary and self-selecting, which do little to overcome the barriers to participation by traditionally absent stakeholders. Rule development thus warrants more systematic focus and attention to ensure that agencies fully engage all relevant stakeholders in each rulemaking in which they have relevant knowledge, experience, or views—thereby promoting the democratic aspirations of regulation. This Article lays the theoretical and practical foundation for more fully democratizing rule development by envisioning what a robust institutional commitment to meaningful public engagement in agenda setting and rule development would entail and developing a structural framework for facilitating quality participation by traditionally absent stakeholders during these crucial early stages of rulemaking. Democratizing rule development would not only improve the quality and legitimacy of agency rules, it could also help to build a culture of civic participation to address the ailing health of our American democracy.
Keywords: Rulemaking; Administrative law; Civic participation; Regulatory agenda setting; Rule development; Regulatory governance